The reflective leader : reflexivity in practice - Robson, Ian (Emerald Publishing Limited, 2022)
The Reflective Leader brings together theory and core concepts through reflective practice, reflexivity, and experiential learning to crystallize current thinking regarding introspection and contextual intelligence in understanding and improving the effectiveness of leaders. Beginning with an understanding how leaders learn through reflection, researchers will be introduced to the philosophical and historical roots that underpin reflective learning. Chapters then examine the leadership journey, learning and un-learning through reflective practice, the reflexive practicum, practice and praxis, creativity and reflection, and action learning and reflection. Featuring interviews with a wide range of practitioners that present reflections on critical incidents and learning episodes, Robson provides a practical narrative to underpin theoretical discovery. "Reflexivity in practice" connects the experience of practitioners, synthesising theory, practice setting and personal experiential learning to support and inform researchers, students, and reflective professionals.
Keywords: Leadership.; Introspection.; Business & Economics -- Leadership.; Management & management techniques.; elektronické knihy; electronic books